Energetic, exergetic and environmental (3E) analyses of different cooling technologies (wet, dry and hybrid) in a CSP thermal power plant - Cutillas, C. G.; Ruiz, J.; Asfand, Faisal; Patchigolla, Kumar; Lucas, M. (Elsevier, 2021)
This paper deals with the comparison of three condensation systems for the heat dissipation in a solar power plant: wet system, dry system and hybrid system based on the pre-cooling of the air in an adiabatic panel located in the entrance section of a dry system. Energy, exergy and environmental (3E) analyses were conducted to assess the influence of the condensation system on the power plant performance. The Andasol I plant located in Granada (Spain), with a net power capacity of 50 MWe, is used as a real reference case of a concentrated solar power station. The cycle refrigerated with a cooling tower achieves a lower pressure of condensation, followed by the hybrid and dry system. As the pressure decreases, the efficiency of the cycle increases and also the power generated, being 12.60% in the case of cooling tower and 4.65% in the hybrid system with respect the dry condenser. A 71.74% of water usage savings by the hybrid system carries a 7.06% of net power production with regard of the cooling tower configuration. The exergetic performance of the plant is 73.77% for the wet system, 69.21% for the hybrid and 68.46% for the dry system.
Keywords: Solar thermal power plant; Condenser; Hybrid system; Exergy; Water consumption